2018
DOI: 10.1097/md.0000000000013339
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid incidentaloma as a “PAIN” phenomenon— does it always require surgery?

Abstract: A thyroid nodule discovered during imaging study performed due to unrelated thyroid disease is known as a thyroid incidentaloma, while positron emission tomography (PET) associated incidental neoplasm of thyroid is known as a “PAIN” phenomenon.To evaluate which patients with “PAIN” phenomenon should undergo surgery in regards to cytology results.Retrospective review of 4716 patients consecutively admitted and surgically treated in tertiary surgical center. 49 (1.04%) patients with “PAIN” phenomenon were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[ 29 31 32 ] The most common reported malignancy was papillary thyroid cancer and this was similarly found in our study. [ 33 34 ] This novel finding of thyroid malignancy has not been highlighted in previous literatures on HS. Most studies reported the association of thyroid disorders in HS without alluding to thyroid malignancy.…”
Section: Discussionmentioning
confidence: 82%
“…[ 29 31 32 ] The most common reported malignancy was papillary thyroid cancer and this was similarly found in our study. [ 33 34 ] This novel finding of thyroid malignancy has not been highlighted in previous literatures on HS. Most studies reported the association of thyroid disorders in HS without alluding to thyroid malignancy.…”
Section: Discussionmentioning
confidence: 82%
“…All studies but one [ 29 ] were reported in the English language. Nine studies were performed by Asian/Eastern [ 17 20 , 22 24 , 27 , 31 ] and six by Western [ 21 , 25 , 26 , 28 30 ] authors. They were single-center or observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…1. Of these, 289 were screened, 84 were assessed as eligible, and 15 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] were included in the final systematic review and meta-analysis. Table 1 summarizes the quality assessment of the 15 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Easy access to high-frequency ultrasound neck examination or to the other imaging tests results in a high number of newly diagnosed cases of PTC. Many studies based on autopsy evaluations confirm the high number of undiagnosed PTCs [ 5 , 35 ] and have highlighted three main estimated mechanisms that contribute to the increasing rate of newly diagnosed TC entities: opportunistic screening, i.e., palpation of asymptomatic patients with subclinical TC; diagnostic cascade performed in patients with general complaints, and incidental findings during neck imaging tests performed due to non-thyroid gland diseases [ 5 , 36 , 37 ]. In Poland, there are no recommendations for TC screening tests; however, ultrasound examinations of the thyroid and subsequent UG-FNAB are commonly ordered [ 38 ].…”
Section: Discussionmentioning
confidence: 99%